Analysis of rooftop solar impacts on distribution networks - D. W. Almeida; A. H. M. S. M. S. Abeysinghe; J. B. Ekanayake (Ceylon Journal of Science, 2019)
Recently, many countries have focused on generating greener energy. As a result, the number of solar photovoltaic (PV) systems connected to the low voltage network has shown a rapid increase around the world. Many studies are being carried out to analyze the potential impact of high penetration of solar PV on the operation and performance of electricity distribution systems. This study proposes a Monte Carlo based approach to evaluate the impacts of rooftop solar PV on low voltage networks and a case study is presented for a typical unbalanced residential network in Sri Lanka using a three-phase, four wire model. The model has been validated by comparing the load flow simulation results with actual measurements and the validated model has been used to investigate the impact of solar PV on distribution networks. The impacts were analyzed using parameters such as voltage unbalances, neutral currents, voltage and thermal limits. Results illustrate that PV penetration is limited under certain penetration levels due to the violation of some of the parameters. Further how phase balancing could be used to minimize high neutral currents and voltage unbalances is also illustrated.